Effect of sand mining on water quality index of Sg.Pusu - Mamun, Abdullah Al; Yusof, Muhammad Anuar; ,, Md. Nuruzzaman; Salleh, Md Noor; Mohd. Dom, Norlida; M. Amin, Mohd. Zaki; Abu Eusuf, Muhammad; Chowdhury, Ahmed Jalal Khan (2016)
This study was conducted to identify effects of sand mining on the water quality index (WQI) of a small river called Pusu. Seven locations along Sg. Pusu were identified for sampling and analysis of the water quality data. It was observed that the WQI of Pusu River varied between 55 and 65 during dry season and 61 to 70 in wet season. The river falls into Class III category in terms of WQI. However, it exceeds the limit of Class V in terms of Total Suspended Solids (TSS) in both the seasons reaching as high as 1050 mg/L of TSS in dry season and 3100 mg/L in wet season. Such high value is very much alarming for aquatic lives.